Behaviour of multilayered simply supported composite hypar shell roof impacted by a solid striker- A finite element approach - Neogi, Sanjoy Das; Karmakar, Amit; Chakravorty, Dipankar (Journal of Structural Engineering, 2024)
Use of laminated composite in the different weight-sensitive branches of engineering has gained immense popularity due to high stiffness to weight ratio of this material. In spite of this advantage, this material is vulnerable to impact loading due to its low transverse shear strength. Literature review on shell reveals that the impact response of civil engineering shell structures has not received due attention. This paper aims to study the response of multilayered composite skewed hypar shell roof for simply supported boundary conditions and different impact velocities. The modified Hertzian contact law is utilised to compute the contact force and the time dependent equations are solved by Newmark’s time integration algorithm.